2017
DOI: 10.1016/j.quascirev.2016.12.015
|View full text |Cite
|
Sign up to set email alerts
|

River terrace development in the NE Mediterranean region (Syria and Turkey): Patterns in relation to crustal type

Abstract: (2017) 'River terrace development in the NE Mediterranean region (Syria and Turkey) : patterns in relation to crustal type.', Quaternary science reviews., 166 . pp. 307-323. Further information on publisher's website: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 108 publications
(129 reference statements)
1
27
0
1
Order By: Relevance
“…little quartz grains), while SEY11 was dated at 60±5 ka. According to what observed byBridgland et al (2017) about river terrace development in the NE Mediterranean region, the sedimentation phases should correspond to cold periods. In particular,Bridgland et al (2012) observed, in the valleys of the Tigris and Ceyhan in Turkey, the Kebir in Syria and the trans-border rivers Orontes and Euphrates, a regular terrace formation in synchrony with 100 ka climatic cycles to be correlated with MIS 12, 10, 8, 6 and 4-2.…”
mentioning
confidence: 60%
“…little quartz grains), while SEY11 was dated at 60±5 ka. According to what observed byBridgland et al (2017) about river terrace development in the NE Mediterranean region, the sedimentation phases should correspond to cold periods. In particular,Bridgland et al (2012) observed, in the valleys of the Tigris and Ceyhan in Turkey, the Kebir in Syria and the trans-border rivers Orontes and Euphrates, a regular terrace formation in synchrony with 100 ka climatic cycles to be correlated with MIS 12, 10, 8, 6 and 4-2.…”
mentioning
confidence: 60%
“…3D). In previous reviews of the preservation patterns shown by fluvial archives, in which causal linkages have been observed with crustal type, such archives indicative of alternating subsidence and uplift were found to be associated commonly with Early or Middle Proterozoic crustal provinces with thick 'roots' of mafic material at the base of the crust, restricting the thickness of the mobile lower crustal layer Bridgland et al, 2017). In the Sudetes this phenomenon is apparent in basinal areas, which are separated by structural ridges (horsts) of older, generally crystalline rocks (Dyjor, 1986; see above).…”
Section: Relation Of Fluvial Archives To Crustal Typementioning
confidence: 99%
“…3). The alternation between uplift and subsidence implicit in these preservation patterns has been ascribed to the properties of the crust of the EEP; such crust is highly consolidated and relatively cold, with a lower mobile layer of limited thickness (probably a few kilometres at most), making it very much less dynamic than younger crustal types Bridgland and Westaway, 2017;cf. Kutas et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…In the uplifting reach upstream of the Great Hungarian Plain, through the Transdanubian Mountain Range, there seems to have been a terrace formed in most but not all late Middle-Late Pleistocene climate cycles, with both MIS 8 and 6 represented [3,109], as well as being marked by karstic levels within the limestone mountains [110]. Young, dynamic crust also extends throughout the tectonically active Mediterranean region, where terrace staircases, both marine and fluviatile, are found in Italy [17,116], Bulgaria-Greece [5,117,118], and Turkey-Syria [18,119,120]. Turkey straddles the boundary between Europe and Asia, and terrace sequences indicative of particularly rapidly uplifting crust have been detected here in the Mediterranean coastal region from the İskenderun Gulf, east of Adana, through Hatay and into the NW corner of Syria, in the region of Latakia [18].…”
Section: Example Eurasian Records From Areas Of Dynamic Crustmentioning
confidence: 99%
“…In comparison with fluvial sequences, the sedimentary archives from other environments, such as caves and lakes, often represent shorter intervals of time; it is useful to cross-correlate these with fluvial sequences, using biostratigraphy and other proxies. Long sequences of marine terrace deposits are found in some coastal regions (e.g., [17]) and they can usefully be compared with nearby fluvial sequences, often representing interglacials, whereas the latter represent cold-stage aggradations [8,18]. In areas where loess sequences are well developed, often as 'overburden' above fluvial archives, these can be sources of complementary evidence, particularly from intercalated warm-climate palaeosols; as well as the famous occurrences in China [19][20][21], such sequences are well known from central Europe [22][23][24] and northern France (e.g., [25]).…”
Section: Introductionmentioning
confidence: 99%